Determinants of circulating calcitonin value: analysis of thyroid features, demographic data, anthropometric characteristics, comorbidities, medications, and smoking habits in a population with histological full exclusion of medullary thyroid carcinoma - Trimboli, Pierpaolo; Peloni, Giuseppe; Confalonieri, Dorotea; Gamarra, Elena; Piticchio, Tommaso; Frasca, Francesco; Makovac, Petra; Piccardo, Arnoldo; Ruinelli, Lorenzo (Frontiers in Oncology, 2024)
Objective: Calcitonin (Ctn) measurement is crucial for the early diagnosis of medullary thyroid carcinoma (MTC). However, Ctn levels can be skewed/elevated due to other reasons and its upper reference value remains debated. In this field, studies have heterogenous setting, published data controversial, and no evidence has been achieved. Study aim was to evaluate all previously investigated Ctn determinants in a population with histological exclusion of MTC. Methods: The institutional records from 2010 to 2022 were reviewed to select patients with thyroid nodules, undergone total thyroidectomy with histological exclusion of MTC, and tested for Ctn just before surgery. Thyroid features, demographic and anthropometric data, comorbidities, medications, and lifestyle information were collected. Univariate and multivariate analyses were performed. Results: 127 cases were included. Median age on thyroidectomy was 51 years. Median Ctn was 1.04 pg/mL (IQR 1.04-2.77) with two cases having value above 10 pg/mL. In univariate analysis, Ctn was correlated with gender (p<0.001), body weight (p=0.016), height (p=0.031), body surface area (p=0.016), thyroid size (p=0.03), thyroglobulin (p<0.001), and chronic kidney disease (p<0.001). After multivariate analysis, the model with highest accuracy included gender, chronic kidney disease, and TSH with adjusted R-squared of 0.4. Conclusions: This study demonstrates, in a population histologically proven as MTC-free, that Ctn value is mainly influenced by gender, anthropometric/thyroid features, and chronic kidney disease, with further impact of TSH.